Deep learning in gaming and animations : principles and applications - Chaudhary, Vikas; Sharma, Moolchand; Sharma, Prerna; Agarwal, Deevyankar (Boca Raton : CRC Press, 2022)
"Over the last decade, progress in deep learning has had a profound and transformational effect on many complex problems, including speech recognition, machine translation, natural language understanding, and computer vision. As a result, computers can now achieve human-competitive performance in a wide range of perception and recognition tasks. Many of these systems are now available to the programmer via a range of so-called cognitive services. More recently, deep reinforcement learning has achieved ground-breaking success in several complex challenges. This book makes an enormous contribution to this beautiful, vibrant area of study: an area that is developing rapidly both in breadth and depth. Deep learning can cope with a broader range of tasks (and perform those tasks to increasing levels of excellence). This book lays a good foundation for the core concepts and principles of deep learning in gaming and animation, walking the reader through the fundamental ideas with expert ease. The book progresses on the topics in a step-by-step manner. It reinforces theory with a full-fledged pedagogy designed to enhance students' understanding and offer them a practical insight into its applications. Also, some chapters introduce and cover novel ideas about how artificial intelligence, deep learning, and machine learning have changed the world in gaming and animation. It gives us a motivation that AI can also be applied in gaming, and there are limited textbooks in this area. The book we will write will comprehensively address all the aspects of AI & Deep Learning in gaming. Also, each chapter follows a similar structure so that students, teachers, and industry experts can orientate themselves within the text. There are few books in the field of gaming using AI. Our book Deep Learning in Gaming and Animation teaches you how to apply the power of deep learning to build complex reasoning tasks. After exposing you to the foundations of the machine and deep learning, you will use Python to build a bot and then teach it the game's rules. We also focus on how different technologies have revolutionized gaming and animation with various illustrations"--
OCLC-licensed vendor bibliographic record.
Keywords: Object-oriented programming (Computer science); Artificial intelligence; COMPUTERS / Computer Engineering; COMPUTERS / Computer Animation